Use of second-line and beyond maintenance therapies in adult patients with primary immune thrombocytopenia in Europe: a parallel study of six prospective multicenter national registries - Guillaume Moulis; Frederick Chen; Giuseppe Carli; Waleed Ghanima; Karolin Trautmann-Grill; Thomas Stauch; Alexandra Schifferli; Haroon Miah; Manuela Rueter; Lisanna Ghiotto; Riccardo Tomasello; Annabell Georgi; et al. (Haematologica)
Not available.